Trends in the treatment and survival of heart failure patients: a nationwide population‐based study in the Czech Republic. (19th August 2021) - Táborský, Milos; Skála, Tomas; Lazárová, Marie; Aiglová, Renata; Špinar, Jindrich; Špinarová, Lenka; Vítovec, Jiri; Kautzner, Josef; Melenovský, Vojtech; Málek, Filip; Dušek, Ladislav; Jarkovský, Jiri; et al.
Abstract: Aims: A retrospective nationwide observational analysis of diagnoses, procedures, and treatment reported to the Czech National Registry of Reimbursed Health Services between 2012 and 2018. Methods and results: Prevalence of heart failure (HF) patients increased from 176 496 (1679.4 per 100 000 population) in 2012 to 285 745 (2689.0 per 100 000 population) patients in 2018 (mean age 74.4 ± 12.8 years). In the last years, a stable incidence of HF patients was observed (544 per 100 000 population in 2016 vs. 551 per 100 000 population in 2018; P = 0.310). Mortality rate decreased from 20.55% in 2012 to 15.89% in 2018. The number of hospitalized patients remained similar (318.2 per 100 000 population in 2012 vs. 311.8 per 100 000 population in 2018; P = 0.479). The most used drugs were diuretics (173 295; 60.6%) and beta‐blockers (178 823; 62.6%), followed by angiotensin‐converting enzyme inhibitors/angiotensin II receptor blockers (angiotensin‐converting enzyme inhibitors 120.581; 42.2%; angiotensin II receptor blockers 47 216; 16.5%). Even though the whole number of implanted devices in HF patients increased steadily (from 25 205 in 2012 to 45 363 in 2018), the prevalence of all devices (pacemakers and defibrillators) in the HF patients remained about the same (14.3% in 2012; 15.9% in 2018). Conclusions: The study included all patients with HF in the Czech Republic. These are the first nationwide data of HF epidemiology in the Eastern bloc. The incidence of HF remains stable in the last years. Due to aging of the population, the prevalence of HF significantly increased in the last 6 years. Despite a continuous increase in the prevalence of HF and a suboptimal utilization of its pharmacological therapy, mortality decreased, and the number of hospitalized patients remained the same.